Molecular Survey of Toxoplasma gondii Infection in Aborted Fetuses of Sheep in the Iğdır Province of Türkiye - Davut Koca; Özlem Orunç Kılınç; Adnan Ayan; Fatma Ertaş Oğuz; Ali Osman Turgut; Özge Oktay Ayan (Turkish Journal of Agriculture: Food Science and Technology)
Toxoplasma gondii, an obligatory intracellular protozoan parasite, can infect a wide range of warm-blooded animals, including livestock species. T. gondii is a zoonotic protozoan parasite that affects both humans and other warm-blooded animals. The aim of this study was to detect T. gondii by using PCR in the brain tissues of 60 aborted sheep fetuses from the Iğdır Province in Türkiye. For this purpose, 60 brain tissue samples of sheep were collected within the lambing seasons of 2023 in Iğdır, Türkiye. The DNA extraction was performed using the PureLink™ Genomic DNA Mini Kit from brain samples. The PCR was performed with the appropriate primers from the obtained DNA samples. T. gondii was found in the brain (16.6%) samples of aborted sheep fetuses. According to the present study, T. gondii infection can be one of the causes of fetus abortion of sheep in Iğdır province, Türkiye. This result emphasizes the need for vigilance and preventive measures in managing this potential public and animal health concerns.